2021
DOI: 10.1039/d0cc06981g
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric dimethylytterbium and the terminal methyl complex (TptBu,Me)Yb(CH3)(thf)

Abstract: Divalent ytterbium bis(trimethylsilyl)amides [Yb{N(SiMe3)2}2]2 and Yb[N(SiMe3)2]2(thf)2 react with purified methyllithium to amorphous dimethylytterbium [YbMe2]n. The characterisation was performed by 171Yb and 13C CP/MAS NMR spectroscopy as well as by conducting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“… 503 The Sm analogue [Sm{N(SiMe 3 ) 2 } 2 (THF) 2 ] ( 78-Sm ·2THF) was obtained by Evans and co-workers with similar methodologies using [Sm(I) 2 (THF) 2 ] and Na[N(SiMe 3 ) 2 ]. 288 78-Yb can also be synthesized via (1) RT reaction of Yb metal with [Sn{N(SiMe 3 ) 2 } 2 ], 90 (2) RTP reaction of Yb metal with HgPh 2 and HN(SiMe 3 ) 2 , 162 and (3) protonolysis between Yb(Bn) 2 (Bn = CH 2 Ph) and HN(SiMe 3 ) 2 504 ( Scheme 52 ; see section 3.4 for details on RT and RTP methods). All these alternative methods are highly desirable to avoid the presence of alkali metal or halide impurities.…”
Section: Nitrogen Donorsmentioning
confidence: 99%
See 4 more Smart Citations
“… 503 The Sm analogue [Sm{N(SiMe 3 ) 2 } 2 (THF) 2 ] ( 78-Sm ·2THF) was obtained by Evans and co-workers with similar methodologies using [Sm(I) 2 (THF) 2 ] and Na[N(SiMe 3 ) 2 ]. 288 78-Yb can also be synthesized via (1) RT reaction of Yb metal with [Sn{N(SiMe 3 ) 2 } 2 ], 90 (2) RTP reaction of Yb metal with HgPh 2 and HN(SiMe 3 ) 2 , 162 and (3) protonolysis between Yb(Bn) 2 (Bn = CH 2 Ph) and HN(SiMe 3 ) 2 504 ( Scheme 52 ; see section 3.4 for details on RT and RTP methods). All these alternative methods are highly desirable to avoid the presence of alkali metal or halide impurities.…”
Section: Nitrogen Donorsmentioning
confidence: 99%
“…Salt metathesis reactivity is the most common methodology employed for the synthesis of binary alkyl and aryl complexes ( Scheme 66 , A ), though there are some notable exceptions such as (1) RT reactions with organomercurials and organobismuth reagents for the synthesis of aryl complexes ( Scheme 66 , B ; vide supra , section 3.4 ), 12 (2) donor cleavage reactions from organoaluminate precursors ( Scheme 66 , C ), 631 and (3) transmetalation reactions between amide precursors and MeLi ( Scheme 66 , D ). 504 Saran and co-workers reported the reaction of MeLi and PhLi with RECl 3 (Sc, Y, La, and Pr) in 1970. 632 In the case of reactivity with PhLi, the authors identified Sc(Ph) 3 and Y(Ph) 3 via IR spectroscopy and elemental analysis, though with La and Pr they identified the formation of “ate” complex LiLa(Ph) 4 from analogous reactivity.…”
Section: Organometallic Reagentsmentioning
confidence: 99%
See 3 more Smart Citations